(untitled) (Studia Prawnicze / The Legal Studies, 2023)
Procedural regulations that provide a citizen with easily accessible, quick and efficatious protection, of his rights are one of the basic questions ensuing from the protection of the consumer. The traditional system of protection where a person concerned is required to take action in order to put its mechanisms and measures in motion (this is, in fact, how the existing civil law judical protection functions) becomes ineffective under the circumstances of opaque market, where both the consumer and the contracting party are not on equal terms, since the latter is better organized and experienced in transactions of various kinds. Consequently, the consumer becomes confused by his inferior position towards the producer, dealer, or the party rendering services and this results in a blocade of instruments provided for his protection. Moreover, he is neither aware of his rights nor strong enough to exercise them, since this is frequently time consuming and ardous. Therefore the protection mechanisms become formalized — being merely potentially at the disposal of the person concerned. The shortcomings of the consumer protection are due to, among others, the deteriorated efficiency of the civil law mechanisms provided to protect the consumer in the market, and this should be improved. In this connection three opinions are presented below, since they concern the discussed problems. The first study is a concise introduction into the subject matter and points to the complexity of problems ensuing from the procedural protection of the consumer, as well as to a great number of possible measures to improve the status quo, the more so that in this respect there exist proposals, constructions and trends in other legal systems. The two remaining studies are of a more analytic nature and deal with specified questions. The article by S. Piątek sheds some light on complaints-handling procedures, and how they relate to the consumer protection by civil law — from the point of view of a specialist in administrative law. The study by F. Zedler pertains to the same subject, which is considered controvelsial by specialists in the administrative and civil law. He tackles this problem from the point of view of both principles of judicial proceedings provided by civil law, and jurisprudence, as related to judicial proceedings. Further on the author analyses the existing system of the consumer protection against the administrative execution of dues from state enterprises. In the final part of the study it is assessed if claims put before courts by consumers are effective, next precise postulates of improvements and changes in this respect are put forward, which are similar to certain trains signalled by K. Piasecki in the first study.